2021
DOI: 10.1055/s-0041-1735299
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Clinical and Laboratory Diagnosis of Abnormal Vaginal Discharge in Chilean Women

Abstract: Objective To determine the concordance between the clinical diagnosis of women with abnormal vaginal discharge (AVD) and laboratory results using molecular detection and observation of the vaginal microbiota. Methods Cross-sectional study conducted in 2018 in Temuco, Chile. A total of 25 midwives from 12 health centers participated. A total of 125 women > 18 years old, volunteers, were recruited. The sample of the posterior vaginal fornix was obtained by speculoscopy. Characteristics of the discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…In contrast, another study illustrated that biofilms related to VVC may act as a reservoir for Chlamydia trachomatis [3]. STIs have been suggested in other studies as risk factor for VVC; however, this relationship should be further confirmed [45,46]. In our study, like most other studies looking at the species distribution of Candida, the most prevalent Candida species isolated was C. albicans, followed by C. glabrata [47,48].…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In contrast, another study illustrated that biofilms related to VVC may act as a reservoir for Chlamydia trachomatis [3]. STIs have been suggested in other studies as risk factor for VVC; however, this relationship should be further confirmed [45,46]. In our study, like most other studies looking at the species distribution of Candida, the most prevalent Candida species isolated was C. albicans, followed by C. glabrata [47,48].…”
Section: Discussionsupporting
confidence: 46%
“…In contrast, another study illustrated that biofilms related to VVC may act as a reservoir for Chlamydia trachomatis [ 3 ]. STIs have been suggested in other studies as risk factor for VVC; however, this relationship should be further confirmed [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, expensive laboratory tests and the extended waiting period remain an obstacle to initiating targeted treatment, hence the importance of a therapeutic combination that is effective on all these germs. We believe that combined kit including Azythromycin, Fluconazole and Secnidazole could fulfill this role [15] [16].…”
Section: Discussionmentioning
confidence: 95%
“…Parte dessa disfunção advém de um crescimento excessivo de lactobacilos. Apesar de manterem o pH vaginal adequado (4,0 -4,5%), protegendo a microbiota vaginal contra infecções causadas por agentes como a E. coli, Candida spp., Gardnerella vaginalis e Mobilincus spp., os lactobacilos isolados ou combinados com outras bactérias, podem gerar um dano ao epitélio vaginal intermediário e resultar em um desgaste celular expressivo, levando à uma doença chamada vaginose citolítica (VC) (Hacisalihoğlu & Acet, 2021;Melo et al, 2021;Carter et al, 2022).…”
Section: Introductionunclassified